A solution procedure for preemptive multi-mode project scheduling problem with mode changeability to resumption - Afshar-Nadjafi, Behrouz (Applied computing & informatics, 2018)
Extensive research has been devoted to the multi-mode resource constrained project scheduling problem (MRCPSP). However, little attention has been paid to problems where preemption is allowed. This paper involves the preemptive multi-mode resource constrained project scheduling problem (P-MRCPSP) to minimize the project makespan subject to mode changeability after preemption. This problem is a more realistic model and extended case of multi-mode resource constrained project scheduling problem. A binary integer programing formulation is proposed for the problem. The problem formed in this way is an NP-hard one forcing us to use the Simulated Annealing (SA) algorithm to obtain a global optimum solution or at least a satisfying one. The performance of the proposed algorithm is evaluated on 480 test problems by statistically comparing in term of the objective function and computational times. The obtained computational results indicate that the proposed algorithm is efficient and effective. Also, it is concluded from the results that mode change is very effective to improve the optimal makespan of the project.